CdSe and ZnSe quantum dots capped with PEA for screening C-reactive protein in human serum. - Gomes, Diana; Algarra, Manuel; Diez de los Ríos, MJ; Arrebola, María Monsalud; Herrera-Gutiérrez, Manuel Enrique; Seller Pérez, Gemma Luisa; Esteves Da Silva, Joaquim C.G. (Elsevier, 2012)
A fluorescence chemical sensor for C-reactive protein (CRP) was developed based on the selective interaction with CdSe and ZnSe quantum dots (QDs) coated with O-phosphorylethanolamine (PEA). Synthesis procedure and analytical parameters such as pH and ionic strength were studied. The decrease in the fluorescence emission intensity was explained due to the specific interaction of the QDs-PEA with CRP, and a correlation was observed between the quenching of the fluorescence and the concentration of CRP. The accuracy of the proposed method was 0.37% as RSD. The proposed method was applied to screen serum samples, and showed to be sensible at the C-reactive protein concentrations of risks levels.
https://openpolicyfinder.jisc.ac.uk/id/publication/17159
Keywords: Proteína C reactiva; Sangre - Análisis; C-Reactive protein; Quantum-dots